119 Disrupting the cycle of adverse childhood experiences by supporting mothers with addiction. (19th August 2020) - Gander, Sarah; Campbell, Sarah; Flood, Kathryn
Abstract: Introduction/Background: Adverse childhood experiences (ACEs), including exposure to neglect, abuse and household dysfunction, have been linked to a higher risk of addiction and mental illness. As these children grow up and start families of their own, their children are at higher risk for ACEs. Evidence has shown that interventions targeting high-risk families with young children are most effective at disrupting these cyclic mechanisms, especially where maternal addiction is present. Objectives: The purpose of this study is to examine the predominance of generational addiction in a cohort of families impacted by maternal addiction, and to identify the potential risks that are present for the current generation of children, in terms of ACEs. Design/Methods: The Addiction Severity Index (ASI) was administered to women who experienced alcohol- or substance-use disorder during pregnancy. Participants were asked about their family's history of addiction and if anyone in a given category (i.e. maternal grandmother, mother's brother) has been affected by either alcohol- or substance-use disorder. Furthermore, existing conditions that are risk factors for ACEs in the current generation were identified (i.e. addiction, incarceration of a family member, domestic violence, mental illness). Results: Many participants reported that at least one of their maternal (68.9%) or fraternal (42.2%) grandparent was impacted by addiction. The subsequent generation was similarly impacted with most participants reporting the presence of addiction in their father and/or his siblings (88.9%) and their mother and/or her siblings (86.7%) Participants report that they experienced an average of seven ACEs (M = 7.13, SD = 2.501) before their 18th birthday. Of this cohort, 53.35% have been incarcerated at least once, 91.1% have been hit by a sexual partner, and 44.4% have been diagnosed with at least one mental health issue. All participants have personally experienced addiction. Conclusion: The participants of this study are clients of the Parent-Child Assistance Program (PCAP), a three-year intervention that supports families impacted by maternal addiction. Given the results of the current study, it is evident that growing up in a home where addiction is present increases the risk of ACEs and future addiction and mental health issues. The PCAP intervention is designed to disrupt this cycle and help families to create a healthier family environment.